A decade of occupational accidents due to direct or indirect electrical contact in the primary, secondary and tertiary sectors in Spain (2003–2012). Issue 1 (2nd January 2017) - Castillo-Rosa, Juan; Suárez-Cebador, Manuel; Rubio-Romero, Juan Carlos; Aguado, Jose Antonio
Abstract : Occupational accidents caused by electrical contact are a major concern worldwide due to their severe consequences. The study conducted is based on an analysis of the evolution of incidence rates and dependence between variables for 14, 022 electrical accidents occurring in Spain between 2003 and 2012. The results show that electrical accidents as a whole are 3.6 times more likely to have severe consequences than the rest of the accidents in the country. This proportion is even nine times greater in the case of fatal accidents. They also confirm a significant relationship between the severity of this type of accidents and the economic sector in which they occur. On the other hand, there is a positive trend in the reduction of the incidence rate, especially in relation to direct contact, although unexpectedly the rate of accidents due to indirect contact is on the rise. Thus, preventing electrical occupational accidents requires efforts to guarantee adequate training adapted to the needs of workers in the various economic sectors. Furthermore, those responsible for safety should work to implement mechanisms to monitor and control compliance with efficient protective measures against electrical contact.